2022
DOI: 10.47144/phj.v54i4.2156
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake Implications as Risk Factor for Hypertension and Comparison of Three Salt Estimation Methods- Findings From Islamabad, Pakistan

Abstract: Objectives: The study was designed to estimate daily salt intake, its discretionary use in healthy individuals and to validate three common methods for salt estimation in Pakistani population. Methodology: Information on demography and discretionary salt use was collected from healthy adults (>18 years) along with a blood sample, spot and 24 hour urine samples. Sodium, chloride, potassium levels and serum creatinine were measured using standard methods. For daily salt estimation, three common methods i.e. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies from Samoa [31], France [32], the USA [33], Norway [34] reported that the INTERSALT with potassium yielded the lowest mean bias to the predicted group-level salt intake. Similarly, studies from Pakistan [35], Portugal [36] and South Africa [37,38] concluded that none of the included equations (Kawasaki, Tanaka, INTERSALT with potassium and Mage) could predict 24-h salt intake at population level. Consistent to our results, several previous studies reported the presence of proportional biases of spot urinebased equations in the Bland-Altman plots indicating positive or negative correlation of individual difference with the average mean intake [28,31,33,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Samoa [31], France [32], the USA [33], Norway [34] reported that the INTERSALT with potassium yielded the lowest mean bias to the predicted group-level salt intake. Similarly, studies from Pakistan [35], Portugal [36] and South Africa [37,38] concluded that none of the included equations (Kawasaki, Tanaka, INTERSALT with potassium and Mage) could predict 24-h salt intake at population level. Consistent to our results, several previous studies reported the presence of proportional biases of spot urinebased equations in the Bland-Altman plots indicating positive or negative correlation of individual difference with the average mean intake [28,31,33,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%